Handling Narcotics and Drug Abuse in Indonesia from the Perspective of Maqāṣid al-Sharī'ah - Sechan, Deswinta Elsa Luxiana; Al Maliki, Muhammad Alwi; Kurniawan, Cecep Soleh (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2025)
Narcotics and drug abuse is a serious problem that has a wide impact on health, social, and legal stability in Indonesia. For this reason, the government is trying to deal with drug abuse in Indonesia, but it is still not optimal due to various factors. In Maqasid al-syari'ah, the handling must be in accordance with the establishment of Islamic law. This article aims to analyze the handling of drug abuse in Indonesia from the perspective of Maqasid al-Syari'ah. This study employs a juridical normative method, combining a legislative approach and a conceptual approach. Data is collected through legislation, research, books, and journals. The collected data is analyzed deductively. The results of the study show that drug handling policies in Indonesia have accommodated repressive and rehabilitative approaches. However, the implementation of rehabilitation still needs to be strengthened to align more closely with the goals of Maqāṣid al-Sharī’ah, which emphasizes human recovery and protection. Religious, social, and psychological drug handling strategies are also considered effective in preventing early drug abuse and supporting social reintegration for abusers. Thus, drug handling in Indonesia not only emphasizes the law enforcement aspect, but must also be oriented towards the benefit and welfare of the community